Fabrication of Bioethanol via Fermentation from Cellulose of Kepok Banana (Musa Paradisiaca L.) Using Bread's Yeast (Saccharomyces cerevisiae) - Naufal, A. Dzaki; Nasution, Rumondang Bulan (Talenta Publisher, 2022)
Bioethanol has been made by fermentation of the cellulose of Kepok banana stems, where this study went through 3 stages. First-stage isolation of cellulose from Kepok banana prevents using HNO3 and NaNO2, removal of swelling with NaOH and Na2SO3, and bleaching process (bleaching) using NaOCl and H2O2, then functional group analysis was performed with FT-IR. The second stage of cellulose obtained was hydrolysed with 1% HCl for 120 minutes of hydrolysis time. The resulting glucose was analysed by Benedict's reagent and the Luff-Schrool method. The third stage of glucose solution results from fermented hydrolysis using bread yeast (Saccharomyces cerevisiae) with variations in the weight of yeast 5, 6, and 7 grams, and the duration of fermentation is five days. Bioethanol obtained was tested qualitatively using K2CrO7 and H2SO4 reagents and bioethanol characterisation using GC. The study results obtained 10.18% glucose levels, and the highest levels of bioethanol were obtained at 11.27% with 88.53% purity using 7 g of yeast.